Primerjava neželenih učinkov po cepljenje proti pnevmokoku in gripi ali samo po cepljenju s pnevmokoknim cepivom - Sočan, Maja (Zdravstveno varstvo, 2003)
Background: Influenza virus and Streptococcus pneumoniae are important respiratory pathogens. Since immunization with influenza virus and pneumococcal vaccines is recommended in similar population groups, both vaccines can be administered simultaneously. Adverse effects of simultaneous pneumococcal and influenza vaccination were compared to those occurring with pneumoccoccal immunization alone. Methods: Pneumococcal and influenza vaccination or pneumococcal vaccination alone were performed in 1,285 subjects. Demographic data and data on chronic diseases and allergies were collected before the immunization. General and local adverse reactions were recorded for five days following the vaccination. Results: Completed questionnaires were returned by 861 subjects. No statistically significant differences were found between responders and non-responders, except for a lower number of diabetics in the group of responders, and a lower number of allergic subjects among non-responders. There was no statistically significantdifference in the rate of adverse reactions between the subjects vaccinated with one vaccine and those given two vaccines (with one exception).In general, more untoward reactions were recorded in subjects 65 years of age and in women (except for fever and local oedema). No serious adverse reactions were documented. Conclusions: Simultaneous administration of influenza and pneumococcal vaccine does not increase the rate of adverse events compared to vaccination with pneumococcal vaccine alone.
Keywords: cepiva; cepljenje; neželeni učinki; pnevmokoki